(3eQGJH GdhLhO GdCQHYjfjIs - (3YHO GdcQje Hf EHQGgje Hf YHO GdcQje GdLjdj GdUhaj , bWH GdOjf,J (B832 (3g` s
(3ChdgG (B:s
(3hef cJGH eQGJH GdhLhO GdCQHYjf ddTjN GdYGQa HGddg GdeMbb SjOi YHO GdcQje GdLjdi s
(3BNQgG (B:s
(3hGdYed HebJVi YdhegG aEfc JUd HgPG Edi ebUhOc LYdfG Gddg Ydi ePgHge Gdbhje HLGg GdfHi GdcQje hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLejYf s
(3fbhd efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B50 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B313s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdNRGfI GdYGeI HGdQHGW (B_ (3GdeZQH (B(115 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds